Complicated corneal ulceration in cats: diagnosis and treatment outcomes of 80 cases (2014-2018) - ALI, KM; MOSTAFA, AA; SOLIMAN, S (Journal of the Hellenic Veterinary Medical Society, 2021)
The study describes the most common clinical and endoscopic findings associated with complicated corneal ulcers in cats and evaluates the short-term outcomes after surgical interventions. Eighty client-owned cats of different breeds with corneal ulcers were included. Cats were clinically evaluated to initially determine corneal abnormalities. Endoscopic examination of the corneas was performed to determine anterior and posterior segments’ abnormalities. Non-healing superficial ulcer was treated by superficial keratectomy and deep stromal ulcers were treated using conjunctival flaps. Corneal sequestrum were treated by partial keratectomies and conjunctival flaps. Anterior synechiae were treated via peripheral iridectomy and separation of the adhesion between the iris and the inner cornea. Symblepharon were treated by removal of the adhered conjunctival membrane from the cornea. Unresponsive endophthalmitis was treated surgically by exenteration. Outcomes after surgical managements of selected corneal abnormalities were assessed clinically and endoscopically. Non-healing superficial ulcer, deep stromal ulcer with descemetocele, endophthalmitis, symblepharon, corneal sequestration and anterior synechiae with secondary glaucoma and corneal scarring were the recorded complications of corneal ulcer. FHV-1 was a common etiologic factor of corneal ulceration. Persistent corneal scars of varying shape and size developed in cats with deep stromal ulcer, anterior synechiae, and corneal sequestration. Domestic shorthaired and Persian cats were the most predisposed breeds to FHV-1 infection and subsequent corneal ulceration. Management of patients with corneal ulcer would prevent serious complications. No age or sex predisposition to complicated corneal ulceration in cats was noticed.